Melatonin ameliorates ionizing radiation-induced oxidative organ damage in rats - ATASOY, BESTE MELEK; YEGEN, BERRAK; ŞENER, GÖKSEL (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
This study was designed to study the effects of the potential radioprotective properties of pharmacological doses of melatonin against organ damage induced by whole-body irradiation (IR) in rats. A total of 32 male Sprague-Dawley rats were exposed to irradiation performed with a LINAC producing 6 MV photons at a focus 100 cm distant from the skin. Under ketamine anaesthesia, each rat received a single whole-body dose of 800 cGy. Immediately before and after IR, rats were treated with either saline or melatonin (20 mg/kg and 10 mg/kg, ip) and decapitated at 12-h after exposure to irradiation. Another group of rats was followed for 72-h after IR, where melatonin (10 mg/kg, ip) injections were repeated once daily. Tissue levels of malondialdehyde (MDA)an index of lipid peroxidation-, glutathione (GSH)-a key to antioxidant- and myeloperoxidase (MPO) activity-an index of neutrophil infiltration-were estimated in liver, lung, colon and intestinal tissues. The results demonstrate that both 12-h and 72-h following IR, tissue leves of MDA were elevated (p<0.05-0.001), while GSH levels were reduced (p<0.05-0.001) in all organs. On the other hand, melatonin, reduced the levels of MDA and increased the GSH levels significantly, (p<0.05-0.001). MPO activity was increased significantly in the colonic tissue at the both 12-h and 72-h, and in the hepatic tissue at the 72-h following IR, which were reduced by melatonin (p<0.01-0.001). In the lung tissue enzyme activity was decreased at 72nd h of postirradiation. In conclusion, the increase in MDA levels and MPO activity and the concomitant decrease in GSH levels demonstrate the role of oxidative mechanisms in irradiation-induced tissue damage, and melatonin, by its free radical scavenging and antioxidant properties, ameliorates irradiation-induced organ injury. Thus, supplementing cancer patients with adjuvant therapy of melatonin may have some benefit for successful radiotherapy. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: irradiation; lipid peroxidation; glutathione; myeloperoxidase; LIPID-PEROXIDATION; MYELOPEROXIDASE; GLUTATHIONE; MECHANISMS; STRESS